2019
DOI: 10.1152/physiol.00021.2018
|View full text |Cite
|
Sign up to set email alerts
|

Scaling of Motor Output, From Mouse to Humans

Abstract: Appropriate scaling of motor output from mouse to humans is essential. The motoneurons that generate all motor output are, however, very different in rodents compared with humans, being smaller and much more excitable. In contrast, feline motoneurons are more similar to those in humans. These scaling differences need to be taken into account for the use of rodents for translational studies of motor output.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
40
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(46 citation statements)
references
References 76 publications
6
40
0
Order By: Relevance
“…However, the 𝑞 𝑆 𝐸 = 2.4-fold range obtained for cats is consistent with the fold-ranges obtained from rat and mouse data for 𝐷 𝑠𝑜𝑚𝑎 as reported in Table 4, while it underestimates the 4.4-fold range in 𝑆 𝑛𝑒𝑢𝑟𝑜𝑛 values observed in mice. Table 4 finally shows that typical cat MN sizes are larger than in rats and mice respectively, as reviewed by Manuel et al (2019). (Kernell, 1966;Cullheim, 1978;Zwaagstra, B.…”
Section: Scaling Of the Normalized Relationshipsmentioning
confidence: 86%
“…However, the 𝑞 𝑆 𝐸 = 2.4-fold range obtained for cats is consistent with the fold-ranges obtained from rat and mouse data for 𝐷 𝑠𝑜𝑚𝑎 as reported in Table 4, while it underestimates the 4.4-fold range in 𝑆 𝑛𝑒𝑢𝑟𝑜𝑛 values observed in mice. Table 4 finally shows that typical cat MN sizes are larger than in rats and mice respectively, as reviewed by Manuel et al (2019). (Kernell, 1966;Cullheim, 1978;Zwaagstra, B.…”
Section: Scaling Of the Normalized Relationshipsmentioning
confidence: 86%
“…the firing patterns of single units in nXIIts, during singing are unknown (Williams and Nottebohm, 1985;Otchy et al, 2019). However, in many motor systems the electrical intrinsic properties of motor neurons and the biomechanical properties of the innervated muscle fibers are highly tuned (Zhurov and Brezina, 2006;Manuel et al, 2019). For example, the discharge rates of motor neurons typically fall within the range frequencies required to generate summed force responses by the muscle fibers.…”
Section: Discussionmentioning
confidence: 99%
“…However, despite the increasing evidence of intensity-dependent PIC amplification, it is still not known whether this phenomenon exists in human motor neurones. Although the extrapolation of gain-control physiology from animal preparations or computational simulations to human physiology are comprehensible, it has been shown that PIC amplification varies between animals and within muscle groups 9,15,[19][20][21][22] , so direct testing across human muscles is needed 23,24 . In fact, two recent studies 23,24 reported no differences in the PIC amplitudes (estimated through paired-motor unit ΔF analysis) across different motor outputs (10%, 20%, and 30% of maximal voluntary force).…”
mentioning
confidence: 99%